Pengaruh Stres Kerja, dan Beban Kerja, terhadap Kinerja Karyawan - Sulastri Sulastri; Onsardi Onsardi (Journal of Management and Bussines (JOMB), 2020)
This study emphasizes the analysis of work stress and workload on employee performance. The research method used is the saturated sample method using multiple analysis techniques. Work Strees Research Results research value t_hit <t_ (α / 2) (-6,829 <2.0422) and (sig α = 0,000 <0.050), this indicates a significant negative relationship between Work Strees (X1) on employee work results. Based on the t_hit test for workload variables (X_2), namely t_hit <t_ (α / 2) (-2,461 <2.0422) and (sig α = 0.021 <0.050), this shows that there are significant negative differences between workloads and professional performance at the Honda Astra Motor Dealer Bengkulu City. Conclusion, the most dominant variable influencing employee performance (Y) is work stress (X1). Keywords: Workload, Employee Performance, Job Stress